Manganese activates autophagy to alleviate endoplasmic reticulum stress–induced apoptosis via PERK pathway - Liu, Chang; Yan, Dong‐Ying; Wang, Can; Ma, Zhuo; Deng, Yu; Liu, Wei; Xu, Bin (Journal of cellular and molecular medicine, 2020)
Overexposure to manganese (Mn) is neurotoxic. Our previous research has demonstrated that the interaction of endoplasmic reticulum (ER) stress and autophagy participates in the early stage of Mn‐mediated neurotoxicity in mouse. However, the mechanisms of ER stress signalling pathways in the initiation of autophagy remain confused. In the current study, we first validated that ER stress–mediated cell apoptosis is accompanied by autophagy in SH‐SY5Y cells. Then, we found that inhibiting ER stress with 4‐phenylbutyrate (4‐PBA) decreased ER stress–related protein expression and reduced cell apoptosis, whereas blocking autophagy with 3‐methyladenine (3‐MA) increased cell apoptosis. These data indicate that protective autophagy was activated to alleviate ER stress–mediated apoptosis. Knockdown of the protein kinase RNA‐like ER kinase (PERK) gene inhibited Mn‐induced autophagy and weakened the interaction between ATF4 and the LC3 promoter. Our results reveal a novel molecular mechanism in which ER stress may regulate autophagy via the PERK/eIF2α/ATF4 signalling pathway. Additionally, Mn may activate protective autophagy to alleviate ER stress–mediated apoptosis via the PERK/eIF2α/ATF4 signalling pathway in SH‐SY5Y cells.